THE IMPACT OF DEEPFAKE TECHNOLOGY ON LEGAL SYSTEMS: A GLOBAL PERSPECTIVE - Kukreti, Abhishek; Kumar, Vivek; Raj, Avishek (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Deepfake technology, a rapidly evolving form of artificial intelligence, allows for the creation of hyper-realistic manipulated media. While deepfakes have gained significant attention for their potential in entertainment and satire, their misuse in criminal activities—such as defamation, political manipulation, and the creation of non-consensual explicit content—has raised urgent legal concerns worldwide. This paper explores the multifaceted challenges posed by deepfake technology on copyright, personality rights, privacy, and defamation law across various jurisdictions, including the United States, India, and the European Union. By examining real-life cases, legal precedents, and recent legislative developments through 2025, this research advocates for the development of comprehensive legislative frameworks to protect individuals against the harmful effects of deepfakes. Additionally, the paper examines emerging technological solutions such as AI-based detection tools, blockchain authentication systems, and international legal cooperation mechanisms to address this evolving threat to legal integrity and individual rights.